The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.matlet.2018.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Improved biodegradation resistance by grain refinement of novel antibacterial ZK30-Cu alloys produced via selective laser melting

Abstract: Cu-containing Mg alloys are a novel type of antibacterial biomaterial based on biodegradation of Mg and antibacterial functions of Cu. However, fast degradation limits their clinical application. For the first time, this work utilizes the synergistic effects of biodegradation of ZK30, antibacterial function of Cu and grain refinement by selective laser melting (SLM) to prepare high-performance antibacterial ZK30-Cu alloys. The obtained alloys have an improved biodegradation resistance, which is attributed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…The layer thickness was controlled by the Z-axial movement of the motion platform. The process parameters were optimized based on our previous work [16] and listed in Table 1. Samples with a diameter of 6 mm and a height of 5 mm were built up, with built layers set up to 100.…”
Section: Methodsmentioning
confidence: 99%
“…The layer thickness was controlled by the Z-axial movement of the motion platform. The process parameters were optimized based on our previous work [16] and listed in Table 1. Samples with a diameter of 6 mm and a height of 5 mm were built up, with built layers set up to 100.…”
Section: Methodsmentioning
confidence: 99%
“…From the point of view of production technology, these properties can be achieved through an optimized heat treatment . 23CrNi3Mo, a Cr–Ni–Mo steel, is widely used as rock drill steel at present, which can be heat‐treated to obtain a good combination of strength and toughness by austenizing, quenching, and tempering, because it contains the alloying elements such as Cr, Ni, and Mo, which promote high hardenability . However, 23CrNi3Mo rock drill tools often suffer early failure, such as brittle failure or fatigue failure even though there has been relatively little wear .…”
Section: Chemical Compositions Of the Experimental Steel (In Wt%)mentioning
confidence: 99%
“…Furthermore, mechanical properties may be improved by alloying and grain refinement. Previous work indicated that ZK30 (Mg-3Zn-0.5Zr) had good mechanical properties and biodegradation resistance[ 13 , 23 ]. When Cu was added to ZK30 by SLM, SLMed ZK30-0.2Cu had a uniform microstructure, good cytocompatibility, and antibacterial performance[ 23 ].…”
Section: Introductionmentioning
confidence: 99%